Taste, salt consumption, and local explanations around hypertension in a rural population in Northern Peru - Amalia Pesantes M. (2017)
Interventions to promote behaviors to reduce sodium intake require messages tailored to local understandings of the relationship between what we eat and our health. We studied local explanations about hypertension, the relationship between local diet, salt intake, and health status, and participants’ opinions about changing food habits. This study provided inputs for a social marketing campaign in Peru promoting the use of a salt substitute containing less sodium than regular salt. Qualitative methods (focus groups and in-depth interviews) were utilized with local populations, people with hypertension, and health personnel in six rural villages. Participants were 18–65 years old, 41% men. Participants established a direct relationship between emotions and hypertension, regardless of age, gender, and hypertension status. Those without hypertension established a connection between eating too much/eating fried food and health status but not between salt consumption and hypertension. Participants rejected dietary changes. Economic barriers and high appreciation of local culinary traditions were the main reasons for this. It is the conclusion of this paper that introducing and promoting salt substitutes require creative strategies that need to acknowledge local explanatory disease models such as the strong association between emotional wellbeing and hypertension, give a positive spin to changing food habits, and resist the “common sense” strategy of information provision around the causal connection between salt consumption and hypertension.